Systemic inflammation during the first year of life is associated with brain functional connectivity and future cognitive outcomes. (February 2022) - Bach, Ashley M.; Xie, Wanze; Piazzoli, Laura; Jensen, Sarah K.G.; Afreen, Sajia; Haque, Rashidul; Petri, William A.; Nelson, Charles A.
Abstract: The first years of life are a sensitive period of rapid neural and immune system development vulnerable to the impact of adverse experiences. Several studies support inflammation as a consequence of various adversities and an exposure negatively associated with developmental outcomes. The mechanism by which systemic inflammation may affect brain development and later cognitive outcomes remains unclear. In this longitudinal cohort study, we examine the associations between recurrent systemic inflammation, defined as C-reactive protein elevation on ≥ 2 of 4 measurements across the first year of life, electroencephalography (EEG) functional connectivity (FC) at 36 months, and composite cognitive outcomes at 3, 4, and 5 years among 122 children living in a limited-resource setting in Dhaka, Bangladesh. Recurrent systemic inflammation during the first year of life is significantly negatively associated with cognitive outcomes at 3, 4, and 5 years, after accounting for stunting and family care indicators (a measure of stimulation in the home environment). Recurrent systemic inflammation is significantly positively associated with parietal-occipital FC in the Beta band at 36 months, which in turn is significantly negatively associated with composite cognitive scores at 3 and 4 years. However, FC does not mediate the relationship between recurrent systemic inflammation and cognitive outcomes.